Securing airway in a burn patient with inhalation injury - A narrow escape - Utsav Acharya; Santosh Bikram Bhandari (Wolters Kluwer Medknow Publications, 2019)
Inhaltion injury is one of the major determinants of the outcome, morbidity and mortality in burn patients. Early intervention to secure the airway in a suspected inhalation injury proves vital in the management and outcome of such patients. Failure to identify such cases will push the attending physicians into a vortex and the patients will succumb to the injury. High degree of suspicion and the ability to identify airway burns is a must for all physicians involved in the management of burn patients. Here we present a case of inhalation injury where airway management was delayed by a few hours due to technical and logistic issues, where in we had a very hard time securing the airway.